Enforcement of Legal Sanctions for Performers of Illegal Mineral and Brain Mining C (Sand) in The Serayu River (Case Study of Sand Mining in Kaliori Village, Kalibagor District, Banyumas Regency) - Risky Dewi Amalia (UM Purwokerto Press, 2023)
Indonesia is a country with abundant natural resources, including the potential sand mining industry. Mining on a large scale is good for economic growth, but the opposite is true for the environmental impacts. Environmental damage due to exploitation also occurs in Kaliori Village, Kalibagor, Banyumas. Environmental damage due to sand mining has caused problems that must be claimed by all parties. This research examines how the impact caused by sand mining activities on the surrounding environment and how sanctions for parties involved in illegal sand mining. This type of research uses normative juridical and legislative approaches and the data sources used by the author in the research use secondary data sources regarding illegal mining of excavation C. Based on the results of the research, law enforcement against illegal mining that occurs is not in accordance with the applicable laws in law enforcement, the apparatus only makes preventive efforts while the community in Kaliori Village has factors such as lack of legal awareness, economic factors and education. Therefore, there is a need for research on environmental impact assessment, both physical and socio-economic sand mining activities in Kaliori Village, in order to obtain an overview of the environmental impacts that occur or will occur. Later, this research will become a consideration in making policies related to sand mining issues.